Corporate governance mechanisms and firm performance in a developing country. Issue 2 (30th March 2020) - Puni, Albert; Anlesinya, Alex
Abstract : Purpose: The purpose of this study is to examine the influence of corporate governance mechanisms recommended by the Securities and Exchange Commission (SEC) of Ghana on firm performance as measured by accounting-based ratios (return on assets, return on equity and earning per share) as well as market-based measure (Tobin's Q) among listed Ghanaian companies from 2006 to 2018. These mechanisms are: board composition (board size, inside directors and outside directors), board committees (audit, remuneration and nomination), chief executive officer (CEO) duality/separation, board meetings and shareholder concentration. Design/methodology/approach: The study used panel regression analysis of data from 38 listed firms in Ghana from 2006 to 2018 to test how each corporate governance variable initiated by the SEC of Ghana contributed to firm performance. Data were extracted from the annual reports of listed companies. Findings: The study found that the presence of both insiders and outsiders on the corporate board improved financial performance. Similarly, board size, frequency of board meetings and shareholder concentration/ownership structure generally had a positive impact on financial performance. However, the presence of board committees generally had a negative impact on financial performance while CEO duality had no impact on financial performance. Practical implications: The study contributes to the understanding of how good corporate governance practices affect firm performance for both academics and particularly Ghanaian policymakers. Originality/value: This study provided new findings to bridge the gaps in the general corporate governance literature relative to the lack of consensus on financial impacts of corporate governance mechanisms. The finding contributes to knowledge by providing new and original evidence that some current corporate governance mechanisms are not effective in minimizing the agency problem in a developing setting. Furthermore, the authors anticipate that the outcomes of this research, which so far is the most comprehensive study in the Ghanaian context in terms of the coverage of corporate governance mechanisms specified by the SEC of Ghana, can significantly shape corporate governance discourse, practices and policies in Ghana, particularly and in other developing countries generally to improve financial performance and corporate sustainability.